2004
DOI: 10.1016/j.fluiddyn.2004.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of sediment suspensions in oscillating grid turbulence

Abstract: A k -model is used to describe the steady state of ÿne-grained sediments maintained in suspension by purely di usive turbulence, as generated in oscillating grid turbulence experiments. The behaviour is shown to depend both on the bulk Rouse number Rou 0 and the product of the bulk Rouse number and the bulk Richardson number Ri 0 Rou 0 , built on oscillating grid parameters. For Rou 0 ¡ 0:01, concentrated suspensions are observed with a homogeneous particle concentration in the suspension layer. An interface, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…(27), we just refer to the qualitative resemblance of the distributions depicted in Fig. 2 with the similar observed and/or modelled distributions published in Kirby & Parker (1983), E & Hopfinger (1989), Noh & Fernando (1991) and Michallett & Mory (2004).…”
Section: D"supporting
confidence: 53%
See 2 more Smart Citations
“…(27), we just refer to the qualitative resemblance of the distributions depicted in Fig. 2 with the similar observed and/or modelled distributions published in Kirby & Parker (1983), E & Hopfinger (1989), Noh & Fernando (1991) and Michallett & Mory (2004).…”
Section: D"supporting
confidence: 53%
“…The major disadvantage of these approaches has been insufficient physical justification of the adopted dependences, revealed mostly in attempts to explain the concentration distributions with the presence of the lutocline. The lutocline was first observed in data measured in the Severn Estuary and Inner Bristol Channel (Kirby & Parker 1983) and was thereafter studied in several experimental (Kirby 1986(Kirby , 1992Mehta 1988;E & Hopfinger 1989;Wolanski et al 1989;Mehta & Srinivas 1993) and model investigations performed on semi-empirical background (Smith & Kirby 1989;Gross & Nowell 1990;Noh & Fernando 1991;Toorman & Berlamont 1993;Michallett & Mory 2004;Yoon & Kang 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an example was given by Matsunaga et al (1999), who reported that the turbulent kinetic energy and dissipation rate of OGT could be computed from the k-ε turbulence model, and their analysis appeared in good agreement with experimental data. Michallet and Mory (2004) also extended the k-ε model to the study of sediment suspension induced by OGT. However, uncertainties could be involved in using k-ε model which is developed largely based on the characteristics of shear-affected flow for this purpose.…”
Section: Summary and Suggestions For Future Studymentioning
confidence: 99%
“…While the first distribution type has been modelled by simple semi-empirical means [1,2,10,11,19,24], then the mathematical models of the second distribution type have required a more thorough physical reasoning. The Prandtl mixing length conception and the k−ε-type turbulence models [5,11,15,17,23] have been applied for this purpose hitherto. Unlike the quoted approaches applying traditional methods of the turbulence problem discussion, the current paper utilizes the theory of the rotationally anisotropic turbulence (RAT theory) [6].…”
Section: Introductionmentioning
confidence: 99%